2017
DOI: 10.1016/j.envpol.2017.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating current and past PCB and PCDD/F sources: The role of a large contaminated soil site in an industrialized city area

Abstract: Cities and contaminated areas can be primary or secondary sources of polychlorinated biphenyls (PCBs), dibenzo-p-dioxins (PCDDs), dibenzofurans (PCDFs), and other chemicals, into air and soil and can influence the regional level of some of these pollutants. In a contaminated site, the evaluation of such emissions can be crucial in the choice of the remediation technology to be adopted. In the city of Brescia (Northern Italy), more than 100 ha of agricultural areas were contaminated with PCBs, PCDD/Fs and heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…In a previous work (Di Guardo et al, 2017) we suggested that soil pollutant profiles of different former agricultural fields in the SIN Caffaro acted as drivers of the bacterial community composition. Here we demonstrated that in one of the previously analyzed fields, the rhizosphere effect of spontaneous plants adapted to the occurring soil contamination significantly influenced bacterial assemblages in the root-associated soil fraction, R and S. We speculate that in the rhizosphere an enhanced pollutant degradation, according to the higher abundance of taxa previously associated to PCB metabolism, contributed to shape bacterial diversity (Leewis et al, 2016a; Ridl et al, 2016).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In a previous work (Di Guardo et al, 2017) we suggested that soil pollutant profiles of different former agricultural fields in the SIN Caffaro acted as drivers of the bacterial community composition. Here we demonstrated that in one of the previously analyzed fields, the rhizosphere effect of spontaneous plants adapted to the occurring soil contamination significantly influenced bacterial assemblages in the root-associated soil fraction, R and S. We speculate that in the rhizosphere an enhanced pollutant degradation, according to the higher abundance of taxa previously associated to PCB metabolism, contributed to shape bacterial diversity (Leewis et al, 2016a; Ridl et al, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, a significant fraction of isolates tolerated moderate saline, osmotic and temperature stresses. These phenotypes are not directly related to PGP or biodegradation activity, but could confer to the strains a higher fitness in soils with complex and uneven pollutant fingerprints and subjected to seasonal changes (Di Guardo et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, intensive agriculture is responsible for the degradation of the quality of surfaceand groundwater, including contamination from pesticides and nitrates (Di Guardo and Finizio, 2016;Di Guardo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%